Age differences in emotion perception in a multiple target setting: an eye-tracking study - Mertens, Alica; Voß, Andreas; Spaniol, Julia; Hische, Amelie; Sauer, Nicola (Emotion, 2020)
Research focusing on the association between age and emotion perception has revealed inconsistent findings, with some support for an age-related positivity effect, as predicted by socioemotional selectivity theory. We used the mood-of-the-crowd (MoC) task to investigate whether older adults judge a crowd consisting of happy and angry expressions to be dominated by happy faces more frequently. The task was to decide whether an array of faces included more angry or more happy faces. Accuracy, response times, and gaze movements were analyzed to test the hypothesis, derived from socioemotional selectivity theory, that age would be associated with a bias toward judging crowds as happy, and with longer and more numerous fixations on happy expressions. Seventy-six participants took part in the study representing 3 different age groups (young, middle-aged, old). Contrary to the hypothesis, older participants more often judged the emotional crowd to be angry compared with younger participants. Furthermore, whereas fixations were longer for happy faces than for angry faces in younger adults, this difference was not present in older adults. A decline in inhibitory processing in older adults as well as higher cognitive demands of the task are discussed as possible explanations for these findings.